ALR-LoRaWAN: An Application-Level Retransmission Management Algorithm for LoRaWAN Networks - Pastório, João; Castro e Souza, Álvaro Ricieri; Spanhol, Fabio; Huff, Alexandre; Camargo, Edson Tavares De (Anais do Latin-American Symposium on Dependable Computing (LADC); 2023: Anais do XII Latin-American Symposium on Dependable Computing, 2023)
LoRaWAN stands out among wireless networking technologies related to the Internet of Things because it operates in an open frequency range and covers long distances with low power consumption and low equipment costs. However, electromagnetic wave obstacles such as tall buildings or valleys affect the signal quality and cause loss of messages exchanged between end devices and the gateway. In addition, message loss may occur on a mobile device due to insufficient network coverage in certain locations along the route. Since the LoRaWAN protocol does not guarantee the delivery of messages, an algorithm is required to manage the retransmission of all undelivered messages. In this paper, we propose the ALR-LoRaWAN algorithm. ALR-LoRaWAN operates at the application layer and uses bidirectional communication between the end device and the IoT application. The algorithm is empirically evaluated and compared with the CR-LoRaWAN algorithm. In CR-LoRaWAN, the management of retransmissions is the responsibility of the network server. Results show that ALR-LoRaWAN successfully processed all lost messages, while CR-LoRaWAN could process at most 36% of the lost messages.